(untitled) (The Research of Medical Science Review, 2025)
Introduction and Objectives: A raise in the demand of Caesarean section procedures in Pakistan specially in Punjab region has raised significant concern because of its complications effecting maternal health. This study was aimed to check the prevalence of this procedure, and identify the potential risk factors and its association in raising the post-operative complications in a secondary healthcare setup. Material and Methodology: A total of 210 women undergoing caesarean section procedures were included in observational cohort study conducted at District Headquarter Hospital Muzaffargarh during July2024-December 2024. Data was collected through a questionnaire developed addressing study objectives related questions including prevalence of C-section, medical history, Reason of procedure, intraoperative and post operative complications, and follow up. Data obtained was entered categorically and statistically analysed using SPSS26. Results: Among 210 women undergoing procedure, 191(91%) of women underwent emergency caesarean section followed by elective caesarean section 19(9%). Haemorrhage 63(30%) was most commonly observed followed by infections 26(12.3%) and post-partum severe pain among 23(10.9%) patients only. Haemorrhage was observed in hypertensive women while infections were observed mostly in diabetic women. Severe pain was mostly reported in the women who had any previous clinical conditions requiring emergency surgery. Conclusion: A significant prevalence of post-caesarean section complications, and identification and management of associated risk factors like diabetes, hypertension, history of previous C-section and mode of anaesthesia not only provide with opportunity to overcome these issues but also emphasizes to confine this procedure to medical indications only.